EMOTIONAL INTELLECTUALITY AND SOCIALPSYCHOLOGICAL FEATURES IN THE PROCESS OFSATISFACTION WITH FAMILY LIFE - Dilorom Oymatova (Euro Asian Journal Publishing, 2025)
This article analyzes the relationship between emotional intelligence (EI) and the level of satisfaction with family life from a socio-psychological perspective. The study highlights the importance of empathy in family life quality, emotional regulation and interpersonal relationships. The results show that high levels of emotional intelligence are an important factor in increasing stability, positive climate, and satisfaction in family relationships
Keywords: Emotional intelligence; family satisfaction; socio-psychological characteristics